Probing the electronic and geometric structure of adsorbed porphyrins and fullerenes - Taylor, Simon (2016)
In this thesis, the geometric and electronic structure of tetra(4-bromophenyl) porphyrin (Br4TPP) and H2O@C60/C60 molecules are studied on Cu, Au and Ag surfaces. Developing an understanding of the physics at the single molecule level is not only important to the nanoscience field, but also in future progression towards nanoscale devices.